2019
DOI: 10.1136/jramc-2019-001155
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between obesity and health problems in help-seeking military veterans

Abstract: BackgroundUK Armed Forces (UK AF) veterans may be particularly vulnerable to obesity and its comorbid physical and mental health problems.AimTo examine the relationship between body mass index (BMI), physical health problems, mental health disorders and sociodemographic characteristics in UK AF veterans engaged in psychological treatment.MethodsInformation regarding veteran BMI, demographic characteristics, physical health conditions and mental health problems was collected and analysed using univariate and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…A relationship between mental health status and smoking has previously been reported in military personnel which was confirmed within the current study by just under 40% of treatment-seeking veterans stating they were current smokers 24 35. Over three-quarters of veterans had a body mass index (BMI) showing they were either overweight (39%) or obese (37%) 36. These rates are higher than in the general public and suggested that treatment-seeking veterans were 2–4 times at increased risk of being obese.…”
Section: Introductionsupporting
confidence: 83%
“…A relationship between mental health status and smoking has previously been reported in military personnel which was confirmed within the current study by just under 40% of treatment-seeking veterans stating they were current smokers 24 35. Over three-quarters of veterans had a body mass index (BMI) showing they were either overweight (39%) or obese (37%) 36. These rates are higher than in the general public and suggested that treatment-seeking veterans were 2–4 times at increased risk of being obese.…”
Section: Introductionsupporting
confidence: 83%
“…18 No studies of obesity in UK veterans overall have been identified, although 35.5% of a sample of veterans seeking help for mental health problems were found to be obese. 19 An important finding from our study was the positive association between type 2 diabetes and PTSD, although the nature of our data and natural history of both conditions did not permit the direction of putative causality to be determined. Our finding mirrors that of the US military Millennium Cohort Study, which examined risk factors for developing diabetes and found that baseline PTSD was significantly associated with risk of diabetes (OR 2.07, 95% CI 1.31 to 3.29), similar to our own finding, but that there was no association between diabetes and other mental health conditions or deployment.…”
Section: Discussionmentioning
confidence: 64%
“…The authors concluded that 24% of male and 30% of female soldiers were at increased risk of obesity-related disease, lower than the UK civilian rate of 57% of men and 56% of women 18. No studies of obesity in UK veterans overall have been identified, although 35.5% of a sample of veterans seeking help for mental health problems were found to be obese 19…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] More than 35% prevalence of overweight as well as obesity was also reported among help seeking UK veterans by Williamson et al in 2019. 15 These variations seen in different studies could be because the studies were performed in different geographic locations on veterans belonging to different socio-economic strata having different cultural and dietary habits It seems that the veterans are just not able to maintain the high level of fitness required in service after the retirement and the degree of overweight/obesity seem to match their elderly civil counterparts in India. The personnel of fighting arms are worse off in this aspect as they are supposed to be among physically more fit and active during service and not able to maintain their level of fitness after retirement; may be because maintaining physical fitness is not obligatory post-retirement.…”
Section: Weightmentioning
confidence: 99%